Ermeneutica del dualismo e logica binaria: Ioan Petru Culianu da Mircea Eliade e Ugo Bianchi a Raimondo Lullo - Casadio, Giovanni (Annali di scienze religiose, 2013)
The Romanian scholar of religions Ioan Petru Culianu (1950-1991) trained under Mircea Eliade (1907-1986) and Ugo Bianchi (1922-1995), following an itinerary parallel to that of the present writer. As a historian of religions, he researched topics inherited from his mentors (ecstasies and otherworldly journeys; Gnosticism and dualism) at the beginning of his career. By the end of the 70s, however, and especially after the death of his first mentor in 1986 and his transfer to the University of Chicago in 1989, he found himself dissatisfied with traditional historical approaches and proposed a method, which he himself defined as cognitive, aimed at overcoming the opposing apories of historicism and structuralism by reducing religions (along with the entire human intellectual production) to a merely mental dimension. Consequently, all religions were nothing but mental maps shaped by a morphodynamic process based on the logic of a binary computation involving a sharp distinction between truth and falsehood, similar to the laws governing artificial intelligences. It is our view that Culianu’s cognitive approach - based on a strong epistemology that disregards the fuzzy dimension of concrete human realities - seems to be an inadequate hermeneutical system for explaining the complexity of the processes of historical-religious formation, as is generally the case with all the approaches included in the category known as the ‘cognitive science of religion’.